'Candidatus Viridilinea mediisalina', a novel phototrophic Chloroflexi bacterium from a Siberian soda lake. Issue 5 (25th February 2019) - Gaisin, Vasil A; Burganskaya, Ekaterina I; Grouzdev, Denis S; Ashikhmin, Aleksandr A; Kostrikina, Nadezda A; Bryantseva, Irina A; Koziaeva, Veronika V; Gorlenko, Vladimir M
ABSTRACT: In this article, we present the description of a novel mesophilic phototrophic Chloroflexi bacterium, ' Candidatus Viridilinea mediisalina' Kir15–3F. We have isolated an anaerobic, highly enriched culture of this bacterium from the Kiran soda lake (Siberia) and optimized its cultivation. Metagenomic sequencing revealed that ' Ca . Viridilinea mediisalina' Kir15–3F is a bacteriochlorophyll-containing Chloroflexi bacterium in the enrichment culture. Fluorescent in situ hybridisation demonstrated a link between the phenotype described here and the ' Ca . Viridilinea mediisalina' Kir15–3F genome. Spectrophotometry and high-performance liquid chromatography analyses showed the presence of bacteriochlorophylls d, c and a, as well as lycopene, γ-carotene and β-carotene. Transmission electron microscopy showed chlorosomes, gas vesicles, polyhydroxyalkanoate-like and polyphosphate-like granules. Our results illustrated that ' Ca . Viridilinea mediisalina' Kir15–3F is an alkaliphilic, salt-tolerant, obligately mesophilic, anaerobic, phototrophic bacterium. The genome sequences lack genes of the Calvin cycle and a sulphide:quinone reductase gene for sulphide oxidation. Owing to the lack of an axenic culture and based on the genomic and phenotypic data, we have presented the description of the bacterium in the Candidatus category. Abstract : We present the description of a novel mesophilic phototrophic Chloroflexi bacterium from a Siberian soda lake.